Comparing visual outcomes of nAMD treatment during and after the COVID-19 restrictions period - Mike Y. Chen; Jeanette Du; Brian K. Do; Mohsin H. Ali (PLoS ONE, 2025)
Main objective Compare treatment outcomes of newly diagnosed neovascular age-related macular degeneration (nAMD) during and after the COVID-19 restrictions. Methods This retrospective study at the Retina Group of Washington analyzed nAMD patients treated with anti-VEGF therapy with ≥ 12 months of follow-up. Two groups were identified: 258 subjects diagnosed between March 2020-March 2022 (Group 1) and 376 subjects diagnosed after (Group 2). Primary outcomes were 12-month and final best-corrected visual acuity (BCVA), and number of injections in the first 12 months. Results Initial mean BCVA was 20/71 and 20/68 in Group 1 and Group 2, with median BCVA of 20/60 and 20/50, respectively. At 12 months, mean BCVA improved to 20/65 and 20/54 in Group 1 and Group 2, respectively (p = 0.086). Final mean BCVA was 20/76 for Group 1 and 20/58 for Group 2 (p = 0.010). The mean change in LogMAR BCVA from the time of conversion to last follow-up was + 0.03 for Group 1 and -0.08 for Group 2 (p = 0.007). Group 1 had fewer injections in the first year of therapy (8.67 vs. 9.21, p = 0.004). 38.8% of Group 1 reached BCVA ≥20/40 at 12 months, versus 48.9% for Group 2 (p = 0.011). Conclusion Patients diagnosed during the COVID-19 restrictions period had worse visual outcomes than those diagnosed thereafter. Multiple factors, including, but not limited to reduced treatment frequency, likely contributed to worse visual outcomes.